Dampak Pembelajaran Matematika dengan Model Kooperatif Tipe Teams Games Tournament terhadap Hasil Belajar Matematika Siswa - Darizah, Nur'aini; Handayani, Isnaini Handayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine mathematics learning outcomes of junior high school students through cooperative learning, the types of Teams Games Tournament. This research was carried out in one of the private junior high schools in South Tangerang. All grade VIII students in this school are population as well as research samples. The experimental design was chosen in this quantitative study because the researcher is the teacher in the class. The instruments used are 8 Multiple Choice and 4 Essay that have been tested for validity and reliability. Data analysis was carried out with SPSS Statistics software version 25. The results of the prerequisite analysist, namely the normality and homogeneity test, showed that the two classes were normally distributed and homogeneous. The results of the hypothesis test obtained a value of sig = 0.191 at a significance level of 0.05. Because the sig value > 0.05, Ho was rejected and Ha was accepted, which means that there is a difference in the student’ mathematics learning outcomes of students with cooperative learning, types of the Teams Games Tournament with students who are taught conventionally. This can be seen from the average score of the experimental class of 74.05 which is higher than the control class so that students who are taught with the types of Teams Games Tournament method have better mathematics learning outcomes than students who are taught with the conventional method. Thus, students' mathematics learning outcomes can be improved by implementing cooperative learning of the Teams Games Tournament types. Keywords: Cooperative Learning, Teams Games Tournament, Mathematics Learning Outcomes.